Морфологічні трансформації щитоподібної залози та інтратиреоїдний йод — визначальні чинники поопераційних рецидивів вузлового колоїдного зоба - Шідловський, В. О.; Шідловський, О. В.; Осадчук, Д. В.; Стасів, М. Я. (Clinical Endocrinology and Endocrine Surgery, 2009)
The research studied the morphological changes of the thyroid gland, the level of intra-thyroid iodine of the paranodular tissue, and the macroscopically unaltered tissue of the contralateral lobe of the thyroid after hemithroidectomy. The study found a direct co-relationship between the morphological changes of the thyroid tissue and the level of intra-thyroid iodine. It also revealed that with an increase of lymphoid infiltration and destruction of thyreocytes the level of intra thyroid iodine decreases concurrently and the organification of non organic iodine is disturbed. Such disorder within the parenchymatous stromal synergism form the background for the pathogenesis of node-formation in the thyroid tissue during the postoperative period.